The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/issj.12430
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of impulse buying on hedonic shopping motivation and life satisfaction of online shoppers in the Philippines

Abstract: As the COVID‐19 pandemic spread worldwide, limiting physical interactions, people turned to online shopping as their mode of buying necessities, and Filipinos were not an exception. However, as the lockdowns and restrictions eased, they reverted to pre‐pandemic shopping behaviours, including purchasing items on their whim and impulse. This study then aimed to investigate the role of impulse buying when it intervenes between hedonic shopping motivation and life satisfaction. A total of 388 Gold and Platinum Sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…According to [29], online shopping results from customers browsing e-commerce sites to search for, select, and purchase goods and services to satisfy their needs and desires. If a consumer has high hedonic motivation, there is a possibility that their shopping style will also become more excessive or impulse buying, in line with research by [5,6]. However, different research results were presented by [7], which stated that hedonic shopping motivation did not significantly influence impulsive buying.…”
Section: Literature Reviewsupporting
confidence: 59%
See 1 more Smart Citation
“…According to [29], online shopping results from customers browsing e-commerce sites to search for, select, and purchase goods and services to satisfy their needs and desires. If a consumer has high hedonic motivation, there is a possibility that their shopping style will also become more excessive or impulse buying, in line with research by [5,6]. However, different research results were presented by [7], which stated that hedonic shopping motivation did not significantly influence impulsive buying.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Purchases based on hedonic shopping motivation can encourage consumers to make impulsive purchases. Research by [5] and [6] states that hedonic shopping motivation has a positive and significant effect on impulsive buying, where the higher the hedonic shopping motivation, the higher the impulsive buying that occurs and vice versa. However, different from the results of research by [7] found that hedonic shopping motivation did not significantly influence impulse buying.…”
Section: Introductionmentioning
confidence: 99%
“…Hedonic motivation has a significant and beneficial impact, indicating that users are more inclined to interact with applications when they are looking for pleasurable and satisfying experiences (Mallari, E. F. I., et al, (2023). [88]).…”
Section: Hedonic Motivation and Its Impact On Impulsive Purchasesmentioning
confidence: 99%